Evaluación de tres dosis de miel de caña en la alimentación de tilapia (Oreochromis spp) en la fase de engorda en Jacalurco Puyo - Tite Córdoba, Cristian Alberto (2016)
This research was conducted at the fish farming project on Jacalurco Puyo Pastaza Provincial Government, the main objective was: to evaluate three doses of sugar molasses at feeding of tilapia (Oreochromis spp) in the phase of fattening in Jacalurco Puyo. The completely random design was applied in this research, therefore 100red tilapia were selected (homogeneous): males Oreochromis species, with an initial weight of 85 grams. They were placed in 4 blue pools according to each randomized treatment, establishing four groups of 25 animals in each one, which were applied by different treatment; T1: balanced diet- 200ml of sugar molasses, T2: balanced diet- 150ml of sugar molasses....